Soil-water characteristic surface model of soil-rock mixture - Kui Wang; Ying Hui; Chuan Zhou; Xue Li; Yao Rong (Journal of Mountain Science, 2023)

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Effects of long-term grazing exclusion on vegetation structure, soil water holding capacity, carbon and nitrogen sequestration capacity in an alpine meadow on the Tibetan Plateau - Yong-sheng Yang; Fa-wei Zhang; Xian-rong Xie; Jun-bang Wang; Ying-nian Li; Xiao-tao Huang; Hui-ting Li; Hua-kun Zhou (Journal of Mountain Science, 2023)

Spatial distributions of intra-community tree species under topographically variable conditions - Ting Lv; Rong Zhao; Ning-jie Wang; Lei Xie; Yue-yao Feng; Yao Li; Hui Ding; Yan-ming Fang (Journal of Mountain Science, 2023)

Evaluation of deep learning algorithms for landslide susceptibility mapping in an alpine-gorge area: a case study in Jiuzhaigou County - Di Wang; Rong-hao Yang; Xiao Wang; Shao-da Li; Jun-xiang Tan; Shi-qi Zhang; Shuo-you Wei; Zhang-ye Wu; Chao Chen; Xiao-xia Yang (Journal of Mountain Science, 2023)

Mechanism of progressive failure of a slope with a steep joint under the action of freezing and thawing: model test - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Bo Lu; Xiao-ke Shen; Xiao-wei Wang; Jie-sheng Liu; Liang-liang Wu; Xin-zhou Zhang (Journal of Mountain Science, 2022)

Geochemical characteristics and geological significance of chert nodules in Qixia formation, Pingding Mountain, lower Yangtze Plate - Jun Li; Lu-wang Chen; Chun-ming Hao; Jie Zhang; Song Chen; He-rong Gui (Journal of Mountain Science, 2021)

Model test of the stability degradation of a prestressed anchored rock slope system in a corrosive environment - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Zhi-jun Liu; Bo Lu; Bin Wang; Yu-zhou Jiang; Jie-sheng Liu; Ping Zeng (Journal of Mountain Science, 2020)

Changes in leaf vein traits among vein types of alpine grassland plants on the Tibetan Plateau - Chang-shun Wang; Wang-wang Lyu; Li-li Jiang; Shi-ping Wang; Qi Wang; Fan-dong Meng; Li-rong Zhang (Journal of Mountain Science, 2020)

Stability analysis of slope in strain-softening soils using local arc-length solution scheme - Xiang-rong Wang; Qi-guo Rong; Shu-li Sun; Hui Wang (Journal of Mountain Science, 2017)

Estimation of soil reinforcement by the roots of four post-dam prevailing grass species in the riparian zone of Three Gorges Reservoir, China - Rong-hua Zhong; Xiu-bin He; Yu-hai Bao; Qiang Tang; Jin-zhang Gao; Dan-dan Yan; Ming-feng Wang; Yu Li (Journal of Mountain Science, 2016)

Engineering geological assessment for route selection of railway line in geologically active area: A case study in China - Run-qiu Huang; Yan-rong Li; Ke Qu; Ke Wang (Journal of Mountain Science, 2013)
The Cheng-Lan railway links Chengdu, a central city in Southwestern China, and Lanzhou, a central city in Northwestern China. The railway passes through the Longmenshan fault zone (Wenchuan earthquake happened there on May 12, 2008), Minjiang fault zone, and Dongkunlun fault zone, which are all active. It runs over the Yangtze River and the Yellow River, and crosses high mountains and deep valleys. There exists, along the railway’s alignment, different kinds of strata of hard granite and soft, weak metamorphic rocks such as carbonaceous slate, schist, and phyllite. It is, therefore, a key issue for such an infrastructure construction to assess the engineering geological conditions and risks, so as to mitigate or avoid possible georisks and to offer optional designs. Geological survey and georisk assessment along the railway corridor are carried out. Special attention is given to active faults, earthquakes and seismic zones. Based on these, discussions about geological aspects for route selection of the railway are conducted and countermeasures for georisk control are proposed accordingly. Main conclusions are achieved as follows: (1) Geohazards such as landslides, rockfalls and debries flows dominate both the route selection of the railway and the engineering structures (e.g., tunnels or bridges) adopted; (2) Tunnel has been proved to be an excellent structure for linear engineering in geologically active area; and (3) In the case where avoiding is impractical, necessary protection measures should be taken to engineering slopes in high earthquake intensity areas, especially the area with earthquake of Ms. 8 or greater.

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)